Plenary Conference 5: Proteomics applications in phytochemical research - Rodríguez Cavallo, Erika; Méndez Cuadro, Darío (Revista Productos Naturales, 2022)
Proteomics is the branch of biochemistry that investigates the structure and function of proteins encoded in a genome...